The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1120672120925035
|View full text |Cite
|
Sign up to set email alerts
|

Three-snip punctoplasty versus perforated plugs for management of lacrimal punctal stenosis

Abstract: Purpose To compare rectangular three-snip punctoplasty and polyvinylpyrrolidone-coated perforated punctal plugs for treatment of acquired lacrimal punctal stenosis. Patients and methods In a prospective comparative non-randomized interventional study, 80 eyes with acquired lacrimal punctal stenosis were classified into two groups. Group A was treated by insertion of polyvinylpyrrolidone-coated perforated punctal plugs (FCI ophthalmics)™ and Group B was treated by rectangular three-snip punctoplasty. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…We did a correlation between the previous causes and age; we noted that multiple causes of punctual occlusion related to aging. In addition, the results of Tamer et al [17] revealed that 46 eyes (57.5%) had Grade 1 punctal stenosis, and 34 eyes (42.5%) had Grade 2. Twenty-four eyes (30%) had epiphora Grade 3 and 56 eyes (70%) had epiphora Grade 4.…”
Section: Discussionmentioning
confidence: 95%
“…We did a correlation between the previous causes and age; we noted that multiple causes of punctual occlusion related to aging. In addition, the results of Tamer et al [17] revealed that 46 eyes (57.5%) had Grade 1 punctal stenosis, and 34 eyes (42.5%) had Grade 2. Twenty-four eyes (30%) had epiphora Grade 3 and 56 eyes (70%) had epiphora Grade 4.…”
Section: Discussionmentioning
confidence: 95%
“…Amongst the different punctoplasty procedures described in the literature, rectangular TSP has become popular due to its ability to prevent the disruption of the horizontal canaliculus required for the normal lacrimal pump mechanism, with a success rate that varies between 74.7% and 93.8%. 12,1921 Chak and Irvine 12 reported 93.8% anatomical and 89.8% functional success rates at mean 8.2 months follow-up. However, Ali et al 19 reported that complete resolution of symptoms was achieved in 74.7% of eyes, although 94.3% anatomical success rate a minimum 6 months follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…However, Ali et al 19 reported that complete resolution of symptoms was achieved in 74.7% of eyes, although 94.3% anatomical success rate a minimum 6 months follow-up. Tamer et al 20 demonstrated 90% surgical success, and Singh et al 21 reported 84% anatomical success rates at 6-month follow-up. In general, the variations in the success rates of rectangular TSP may be related to the difference in the follow-up period as the restenosis rate is more likely to increase over time.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding position, no plug dislodgment or migration was found in this study. In the study of Abd El Ghafar et al [ 13 ] two plugs out of 30 (6.7%) had extruded before 6 months postoperatively versus one plug out of 45 plugs within 2 weeks in the study of Ozgur et al [ 14 ], and also one out of 40 during the 1st month in the study of Tamer et al [ 15 ], who reported additional rotation of four plugs (10%) via the slit lamp examination. The perforated plug was designed to have a shorter medial side compared with the lateral side so that its collar has a higher flange towards the temporal side of the lacrimal papillae and a lower one towards the medial side of the punctum in relation to the lacus lacrimalis to ensure better tear drainage.…”
Section: Discussionmentioning
confidence: 99%